Pearson discover history student book 1 - Addison, Penny; Albert, Trish (Pakistan : Pearson (Kifayat publications), 2024)
Pearson Discover History 1 is the first book in a series designed to introduce young learners to key historical concepts and events. Through engaging narratives, illustrations, and activities, it develops an understanding of the past, historical timelines, and important civilizations. The book encourages curiosity, critical thinking, and connections between history and the modern world, making the subject accessible and enjoyable for beginners.
Keywords: History - Text Book